Biotin rescues mitochondrial dysfunction and neurotoxicity in a tauopathy model. - Lohr, K.M.; Frost, B.; Scherzer, C.; Feany, M.B. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Mitochondrial and metabolic dysfunction are often implicated in neurological disease, but effective mechanism-based therapies remain elusive. We performed a genome-scale forward genetic screen in a Drosophila model of tauopathy, a class of neurodegenerative disorders characterized by the accumulation of the protein tau, and identified manipulation of the B-vitamin biotin as a potential therapeutic approach in tauopathy. We show that tau transgenic flies have an innate biotin deficiency due to tau-mediated relaxation of chromatin and consequent aberrant expression of multiple biotin-related genes, disrupting both carboxylase and mitochondrial function. Biotin depletion alone causes mitochondrial pathology and neurodegeneration in both flies and human neurons, implicating mitochondrial dysfunction as a mechanism in biotin deficiency. Finally, carboxylase biotin levels are reduced in mammalian tauopathies, including brains of human Alzheimer's disease patients. These results provide insight into pathogenic mechanisms of human biotin deficiency, the resulting effects on neuronal health, and a potential therapeutic pathway in the treatment of tau-mediated neurotoxicity.